2022-RA-593-ESGO Primary ovarian non-hodgkin lymphoma: report of three cases and the role of international online meetings in clinical decision making. (20th October 2022) - Soliman, Mahmoud; Hassan, Amany; Hamed, Manar; Refky, Basel
Abstract : Introduction/Background: Primary ovarian lymphoma is a rare entity representing 1.5% of ovarian neoplasms. Although ovarian involvement by lymphomatous deposits as a part of disseminated disease is well-recognized, the initial manifestation of lymphoma as an ovarian mass is unusual and unnecessary surgery may be performed. Diagnosis is challenging and lack of sufficient evidence adds to the clinical dilemma. Methodology: We report three cases of primary ovarian diffuse large B cell lymphoma with different scenarios in which clinical decision-making was reinforced through the online International Gynecologic Cancer Society (IGCS) tumor board. Results: The first case was a young patient who presented with weight loss and rapidly progressive abdominal distension. CT scan revealed a large right adnexal mass with smaller left ovarian deposits and ascites along with elevated CA-125 and LDH. Right salpingo-oopherectomy and excision of a small left ovarian deposit showed bilateral ovarian diffuse large B cell lymphoma. Based on tumor board discussions, fertility counseling, oocyte cryopreservation and GnRH analogue were given prior to starting systemic therapy. The second patient had a large right ovarian swelling and unilateral salpingo-oopherectomy confirmed the diagnosis of lymphoma. PET scan after surgery revealed pelvic nodes and peritoneal involvement. Following complete response with chemotherapy, the IGCS online meeting recommended radiotherapy as a consolidation therapy. The third patient had bilateral large ovarian masses and enlarged para-aortic nodes raising the suspicion of metastatic krukenberg tumor versus primary cancer. Complete surgical staging was done and lymphoma of the ovaries, as well as all dissected nodes was found. Conclusion: Primary ovarian lymphoma is rare and is usually misdiagnosed at time of presentation. There is no consensus on optimal management or treatment protocols and most of the data are based on case reports and literature reviews. International multi-disciplinary online tumor boards offer an excellent opportunity to exchange experience and enhance decision-making process.